Understanding adult student stop-out: perspectives of mid-career online graduate students - Gnadt, Amanda S. (Kansas State University, 2023)
The purpose of this qualitative case study is to understand the experiences of adult graduate students who stop-out, or take a break from enrollment, but who ultimately persist by reenrolling. The participants in this study were enrolled in an online master’s degree program. Symbolic interactionism was the theoretical framework for this study using criterion sampling. While findings revealed the individualistic nature of the stop-out experience, there were commonalities among participants. They valued flexibility, convenience of process, and receiving timely information. Graduate programs are encouraged to identify central support personnel, implement reenrollment plans, and acknowledge the silent stop-out.
Keywords: Adult learning; Stop-out; Graduate students; Graduate programs; Online programs